Do Businessmen Make Good Governors? - Florian Neumeier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
This paper empirically evaluates the economic performance of U.S. state governors who came to the position from a business background (CEO governors), focusing on income growth, unemployment, private investment, and income inequality. Methodologically, I apply a matching method to account for the endogeneity of political selection. I find that the tenures of CEO governors are associated with a 0.6 percentage points higher annual income growth rate, a 0.4 pp higher growth rate of the private capital stock, and a 0.6 percentage points lower unemployment rate than are the tenures of non-CEO governors. Income inequality decreases when CEO governors hold office.
Keywords: C21; D31; E24; J60; 330; U.S. Governors; economic growth; unemployment; income inequality; businessmen; entropy balancing.